The Effects of Baby Massage to Sleep Quality in Infant Age 1-7 Months - Saputro, Heri; Bahiya, Choridhatul (Journal for Research in Public Health, 2021)
Sleep quality is very important for infant’s growth and development. Poor sleep quality can lead to decreased daily activity, weakness, anxiety, decreased resistance, so that growth and development is less than optimal. Baby massage is one way to relieve tension and anxiety in the infant, so that it becomes calm, sleep soundly and the power of concentration will be fuller. The purpose of this research to know the effect of baby massage on sleep quality of infants aged 1-7 months in BPM NY. Choridatul Bahiya AMd. Keb Kebonsari Sukun of Malang City. The research design used Quasy experimental designs with non equivalent control group design. The population of all infants aged 1 to 7 months was 25 infants with samples meeting the inclusion criteria of 20 respondents consisting of 10 respondents treatment group and 10 respondents control and taken by purposive sampling. Data were collected using questionnaire and analyzed using wilcoxon match pairs test. The results showed that the quality of infant sleep in the treatment group before being massaged was mostly 8 (80%) poor, 2 infants (20%) moderate and in the control group most were 6 (60%) poor, 3 (30%) were poor and 1 infant (10%) is good. Sleep quality after massaging in the treatment group was mostly 6 (60%) good, 3 (30%) moderate and 1 (10%) bad, whereas in the control group without having a baby massage most of the 6 (60%) were bad, 3 infants (30%) moderate and 1 baby (10%) good. The results showed that there was influence of infant massage on the quality of baby sleep with r value of 0,006 <α (0,05). The results show that baby massage can improve the quality of baby sleep, especially for babies who have poor sleep quality. Therefore health workers should provide counseling to mothers who have babies about infant massage, so motivated in learning to do baby massage independently.